Combinações de laxantes e biomassa de banana verde no tratamento de constipação funcional em crianças e adolescentes: estudo randomizado - Cassettari, Vanessa Mello Granado [UNESP]; Machado, Nilton Carlos [UNESP]; Lourenção, Pedro Luiz Toledo de Arruda [UNESP]; Carvalho, Marry Assis [UNESP]; Ortolan, Erika Veruska Paiva [UNESP] (Elsevier, 2018)
Objectives: Evaluate the effect of combinations of green banana biomass and laxatives in children and adolescents with chronic constipation. Methods: This was a randomized study of 80 children and adolescents with functional constipation according to the Rome IV Criteria, who were divided into five groups: (1) green banana biomass alone; (2) green banana biomass plus PEG 3350 with electrolytes; (3) green banana biomass plus sodium picosulfate; (4) PEG 3350 with electrolytes alone; and (5) sodium picosulfate alone. Primary outcome measure was the reduction of the proportion of patients with Bristol Stool Form Scale ratings 1 or 2. Secondary outcome measures were: increase of the proportion of >3 bowel movements/week and reduction of the proportion of fecal incontinence, straining on defecation, painful defecation, blood in stool, abdominal pain, and decreased laxative doses. Results: On consumption of green banana biomass alone, a statistically significant reduction was observed in the proportion of children with Bristol Stool Form Scale rating 1 or 2, straining on defecation, painful defecation, and abdominal pain. Conversely, no reduction was observed in fecal incontinence episodes/week, blood in stool, and no increase was observed in the proportion of children with >3 bowel movements/week. The percentage of children who required decreased laxative dose was high when green banana biomass was associated with sodium picosulfate (87%), and PEG 3350 with electrolytes (63%). Green banana biomass alone and associated with laxatives was well tolerated, and no adverse effects were reported. Conclusion: Green banana biomass is advantageous as an adjunct therapy on functional constipation, mainly for reducing doses of laxatives.
Combinations of laxatives and green banana biomass on the treatment of functional constipation in children and adolescents: a randomized study
Keywords: Constipation; Dietary fiber; Green banana; Green banana biomass; Resistant starch